Human immunodeficiency virus infection of human brain capillary endothelial cells occurs via a CD4/galactosylceramide-independent mechanism. - Moses, A V (1993)
Neuropathologic studies of AIDS patients have shown that brain capillary endothelial cells are a cellular target for human immunodeficiency virus (HIV) in vivo. We have established in vitro cultures of primary human brain capillary endothelial (HBCE) cells. Using this model system, we have shown a significant HIV infection of HBCE cells that is productive yet noncytopathic. The infection is mediated by a cellular interaction with gp120 that does not involve CD4 or galactosylceramide. HIV infection of HBCE cells may contribute to AIDS-associated neuropathology by disturbing the physiology of the endothelium and directly or indirectly facilitating dissemination of virus to the central nervous system.